In silico approach: biological prediction of nordentatin derivatives as anticancer agent inhibitors in the cAMP pathway. Issue 70 (25th November 2020) - Abdjan, Muhammad Ikhlas; Aminah, Nanik Siti; Siswanto, Imam; Thant, Tin Myo; Kristanti, Alfinda Novi; Takaya, Yoshiaki
Abstract : A combination of computational techniques has been carried out to predict the binding of nordentatin derivatives based on pyranocoumarin semi-synthesis with the target protein from the expression of the PDE4B gene. Abstract : A combination of computational techniques has been carried out to predict the binding of nordentatin derivatives based on pyranocoumarin semi-synthesis with the target protein from the expression of the PDE4B gene. The inhibition of the cAMP pathway is the main target of anti-cancer drugs, which is responsible for uncontrolled cell division in cancer. Modeling was done using a combination of semi-empirical methods and the density functional theory (PM3-DFT/6-31G*/B3LYP) to obtain the optimal structure of a small ligand that could be modeled. Studies on the interaction of the ligands and amino acid residues on protein targets were carried out using a combination of molecular docking and molecular dynamic simulation. Molecular docking based on functional grid scores showed a very good native ligand pose with an RMSD of 0.93 Å in determining the initial coordinates of the ligand–receptor interactions. Furthermore, the amino acid residues responsible for interaction through H-bonds were Tyr103, His104, His177, Met217, and Gln313. The binding free energy (kcal mol −1 ) results of the candidates were PS-1 (−36.84 ± 0.31), PS-2 (−35.34 ± 0.28), PS-3 (−26.65 ± 0.30), PS-5 (−42.66 ± 0.26), PS-7 (−35.33 ± 0.23), and PS-9 (−32.57 ± 0.20), which are smaller than that of the native ligand Z72 (−24.20 ± 0.19), and thus these have good potential as drugs that can inhibit the cAMP pathway. These results provide theoretical information for the efficient inhibition of the cAMP pathway in the future.